Micropropagation of Prunus scoparia, a Suitable Rootstock for Almond under Drought Conditions. Issue 2 (3rd April 2019) - Abbasi, Fatemeh; Khadivi, Ali; Taghizadeh, Mina; ValizadehKaji, Babak
ABSTRACT: Prunus scoparia is a wild deciduous shrub, usually living on dry calcareous soils of the rocky mountains and has been used as a grafting rootstock for domesticated almonds to provide drought resistance. In the current study, micropropagation ability of P. scoparia was investigated using cytokinin and auxin. Uniform nodal shoot pieces (3–5 cm in length) of seedlings were used as explants. The explants were disinfected with 10% sodium hypochlorite solution. For adventitious shoot induction and proliferation, Murashige and Skoog (MS) media containing 7.00 g/l agar and 30.00 g/l sucrose containing five concentrations of benzyl adenine (BA) (0.00, 0.50, 1.00, 2.00, and 4.00 mg/1) and also containing six concentrations of Thidiazuron (TDZ) (0.00, 0.50, 1.00, 2.00, 5.00, and 7.00 mg/1) were compared. For rooting, i n vitro shoots (2–3 cm) were transferred into ½ MS medium supplemented with 30 g/l sucrose, 7.50 g/l agar, and different concentrations of IBA (0.00, 0.25, 0.50, and 1.00 mg/l) and NAA (0.00, 0.25, 0.50, and 1.00 mg/l). Based on the results obtained for shoot proliferation, only 2.00 and 4.00 mg/l BA and 2.00 mg/l TDZ concentrations generated shoots, while other treatments did not show shoot proliferation. Among the three treatments that generated shoots, the best results for shoot number, leaf number, and leaf color quality were observed in media containing 2.00 mg/l TDZ. Based on the results obtained for rooting, the effect of IBA concentrations on the rooting percentage, root number, and root length was significant. Among IBA concentrations, only 0.50 mg/l IBA induced rooting, while there was no rooting in the media containing other IBA concentrations. None of the NAA concentrations showed rooting. In conclusion, MS culture medium supplemented with 2.00 mg/l TDZ and ½ MS culture medium supplemented with 0.50 mg/l IBA are suggested for in vitro shoot proliferation and rooting of P. scoparia, respectively. The results presented herein could be used for in vitro selection and micropropagation of P. scoparia.